1964
DOI: 10.1128/jb.88.5.1288-1295.1964
|View full text |Cite
|
Sign up to set email alerts
|

PURIFICATION AND PROPERTIES OFN-ACETYL-d-GLUCOSAMINE KINASE FROMSTREPTOCOCCUS PYOGENES

Abstract: A kinase from Streptococcus pyogenes which catalyzes adenosine triphosphate-dependent phosphorylation of D-glucose and N-acetyl-D-glucosamine has been purified 1,500-fold. The ratio of the enzymatic activity on both substrates remained constant throughout the fractionation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1964
1964
1984
1984

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…3 and 5 and Table 1 suggest that a single kinase may be responsible for phosphorylation of glucose, N-acetylglucosamine, and glucosamine. Zeleznick et al (9) concluded that both glucose and N-acetylglucosamine are phosphorylated by the same kinase in S. pyogenes; the present results with L. mesenteroides are consistent with that conclusion.…”
Section: Fig 4 Sedimentation Analysis Of Crude Enzyi Extracts Of Lesupporting
confidence: 91%
“…3 and 5 and Table 1 suggest that a single kinase may be responsible for phosphorylation of glucose, N-acetylglucosamine, and glucosamine. Zeleznick et al (9) concluded that both glucose and N-acetylglucosamine are phosphorylated by the same kinase in S. pyogenes; the present results with L. mesenteroides are consistent with that conclusion.…”
Section: Fig 4 Sedimentation Analysis Of Crude Enzyi Extracts Of Lesupporting
confidence: 91%
“…Several investigators have found the intracutaneous test with venom extract useful when investigating insect allergy (22). SPT has been used by others (2).…”
Section: ; -mentioning
confidence: 99%
“…Chitin is formed by extracts of Neurospora with UDP-acetylglucosamine as donor (Glaser & Brown, 1957). Extracts of certain bacteria catalyse rhamnose-transfer from TDP-rhamnose to lipid (Burger, Glaser & Burton, 1962) or to polysaccharide (Zeleznick, Boltralik, Barkulis, Smith & Heymann, 1962).…”
Section: Fourth Hopkins Memorial Lecturementioning
confidence: 99%